Pengaruh Peran Perawat Komunitas terhadap Peningkatan Pengetahuan dan Pola Makan pada Penderita Hipertensi - Natalia Datu; Risnawati Risnawati; Haedir Haedir; Ulvy Pratiwy D; Erwin Erwin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
In Indonesia, hypertension is a prevalent non-communicable condition that can cause major side effects such as renal failure, heart disease, and stroke. High blood pressure prevention can be achieved through improving knowledge and adopting healthy dietary habits. Community nurses play a crucial part in educating people about health enhance the general public knowledge regarding hypertension. This investigation sought to ascertain the influence of community nurses’ roles in improving knowledge about the potential increase in blood pressure related to dietary patterns among patients with hypertension in Buntu Babang Village, Bajo District, Luwu Regency. This study used a cross-sectional, quantitative methodology. 32 respondents that were chosen via accidental sampling made up the sample. The Chi-square test was used to examine the data. The findings demonstrated this community nurses’ roles influenced the improvement of knowledge among patients with hypertension (p = 0.052), while There was no discernible impact on the dietary patterns of hypertensive patients (p = 0.317). In conclusion, community nurses contribute to improving the knowledge of patients with hypertension; however, their role has not significantly influenced dietary trends among patients with hypertension in Buntu Babang Village, Bajo District, Luwu Regency.